2010
DOI: 10.1111/j.1439-0434.2010.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology, Epidemiology and Management of Rhizoctonia solani on Potato

Abstract: Black scurf and stem canker on potato is an economically important disease complex, causing both quantitative and qualitative damage to potato crops which occurs in potato production areas throughout the world. The ribosomal DNA internal transcribed spacer sequence analysis is currently accepted and a commonly used method for classifying Rhizoctonia species and anastomosis groups (AGs). To date, 13 AGs have been recognized. The updated AG distribution in potato worldwide production areas confirm the status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 92 publications
(231 reference statements)
3
99
1
17
Order By: Relevance
“…As noted by Tsror (2010), effective management of R. solani requires the implementation of an integrated disease management approach, and within this approach, cultural practices that decrease inoculum density in the soil are the most important measures. In the first experiment (winter), a lower incidence of symptoms caused by R. solani was observed in the lower N rate in ASP system ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Tsror (2010), effective management of R. solani requires the implementation of an integrated disease management approach, and within this approach, cultural practices that decrease inoculum density in the soil are the most important measures. In the first experiment (winter), a lower incidence of symptoms caused by R. solani was observed in the lower N rate in ASP system ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…And damping-off control requires the implementation of an integrated disease management approach combining both preventive and curative tactics and strategies (Lamichhane et al, 2017;Tsror, 2010). Although ICLS promote changes in the environment, little is known about the influence of different arrangements of these production systems in the occurrence of plant disease, particularly when the forestry component is added.…”
Section: Introductionmentioning
confidence: 99%
“…In northern seed potato production conditions, haulm killing is applied to immature plants and harvest is delayed as long as over 3 weeks after the haulm killing, weather conditions permitting. Tuber crops are known to be exposed to infection by black scurf when the haulm is destroyed while the root system is still in operation and the time between haulm killing and harvest is prolonged (Tsror, 2010). Black scurf caused by R. solani (Kühn AG-3) leads to substantial economic losses (Lootsma & Scholte, 1996), and in seed potato production, it may be an obstacle to certification.…”
Section: Yield and Qualitymentioning
confidence: 99%
“…In contrast, Bains & Bisht (1995) did not observe specific AGs associated with particular climatic regions, and demonstrated that AG-3, AG-4 and AG-5 occurred on infected potato plants grown in a single potato field. Alternative hosts for R. solani may also affect the distribution of the fungus, with solanaceous weeds acting as possible reservoirs for the pathogen (Tsror, 2010).…”
Section: Anastomosis Groups Of Rhizoctonia Solanimentioning
confidence: 99%
“…AGs have been further divided into subgroups, and subgroups into subsets, on the basis of culture morphology, pathogenicity, host range, nutritional requirements and/or biochemical and genetic properties (Stevens Johnk et al, 1993;Kuninaga et al, 1997Kuninaga et al, , 2000bNicoletti et al, 1999;Carling et al, 2002b). Binucleate Rhizoctonia isolates are associated with diseased potato plants, but cause minimal damage when tested on potatoes (Tsror, 2010).…”
Section: Anastomosis Groups Of Rhizoctonia Solanimentioning
confidence: 99%